Ultrashort echo time imaging of the lungs under high‐frequency noninvasive ventilation: A new approach to lung imaging. Issue 6 (28th May 2019) - Delacoste, Jean; Dournes, Gael; Dunet, Vincent; Ogna, Adam; Noirez, Leslie; Simons, Julien; Long, Olivier; Berchier, Grégoire; Stuber, Matthias; Lovis, Alban; Beigelman‐Aubry, Catherine
Abstract : Background: Although ultrashort echo time (UTE) sequences allow excellent assessment of lung parenchyma, image quality remains lower than that of computed tomography (CT). Purpose: To investigate a high‐frequency noninvasive ventilation (HF‐NIV) technique allowing a stabilized inspiration and to compare image quality with current dedicated MR sequences. Study Type: Prospective. Population: Ten healthy volunteers. Field Strength/Sequence: 3D radial UTE sequence at 1.5T. Assessment: UTE‐HF‐NIV sequence was compared with UTE‐free‐breathing (UTE‐FB), reconstructed at end expiration (UTE‐Exp) and average (UTE‐Avg), and breath‐hold VIBE sequences. The distance from lung apex to the dome of the right hemidiaphragm was measured. Visual assessment of the visibility and sharpness of normal anatomical structures was carried out. Dedicated software also quantitatively evaluated vessel–lung and right lung–liver interface sharpness. Apparent signal ratio (Sr) and contrast ratios (Cr) were quantitatively evaluated. Statistical Tests: Wilcoxon signed rank test for visual scores, paired t ‐test for continuous variables, significance at P < 0.05. Results: The distance between apex and the right hemidiaphragmatic dome was significantly larger ( P < 0.001) with UTE‐HF‐NIV compared with UTE‐FB and VIBE acquisitions. Vessel and airway visibility had identical median visual scores with all UTE methods. Median visual scores for sharpness of vessels and airways were significantly higher ( P < 0.001) with HF‐NIV (vessels = 3; airways = 2) than in UTE‐FB (vessels = 2; airways = 1) and VIBE (vessels = 1; airways = 1). Software‐based vessel sharpness evaluation resulted in larger values in 8/10 volunteers with UTE‐HF‐NIV (67.3 ± 9.8) compared with UTE‐Avg (62.3 ± 12.6) but the average difference was not significant ( P = 0.28). The sharpness of the lung–liver interface was significantly higher ( P < 0.001) with HF‐NIV (17.3 ± 5.3) compared with UTE‐Avg (14.1 ± 3.9). Significantly higher values ( P < 0.01) of Sr and Cr were observed with UTE‐HF‐NIV compared with UTE‐FB and VIBE. Data Conclusion: HF‐NIV allowing acquisition at full inspiration significantly improves image quality for lung imaging. This could offer the option to alternate some follow‐up CT studies by using this technique. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:1789–1797.